An in vitro splicing assay reveals the pathogenicity of a novel intronic variant in ATP6V0A4 for autosomal recessive distal renal tubular acidosis - Yamamura, Tomohiko (BMC Nephrol, 2017)
BACKGROUND: Autosomal recessive distal renal tubular acidosis (dRTA) is a rare hereditary disease caused by pathogenic variants in the ATP6V0A4 gene or ATP6V1B1 gene, and characterized by hyperchloremic metabolic acidosis with normal anion gap, hypokalemia, hypercalciuria, hypocitraturia and nephrocalcinosis. Although several intronic nucleotide variants in these genes have been detected, all of them fell in the apparent splice consensus sequence. In general, transcriptional analysis is necessary to determine the effect on function of the novel intronic variants located out of splicing consensus sequences. In recent years, functional splicing analysis using minigene construction was used to assess the pathogenicity of novel intoronic variant in various field. METHODS: We investigated a sporadic case of dRTA with a compound heterozygous mutation in the ATP6V0A4 gene, revealed by next generation sequencing. One variant was already reported as pathogenic; however, the other was a novel variant in intron 11 (c.1029 + 5G > A) falling outside of the apparent splicing consensus sequence. Expression of ATP6V0A4 was not detected in peripheral leukocytes by RT-PCR analysis. Therefore, an in vitro functional splicing study using minigene construction was conducted to analyze the splicing pattern of the novel variant. RESULTS: A minigene assay revealed that the novel intronic variant leads to a 104 bp insertion immediately following exon 11. In addition, this result was confirmed using RNA extracted from the patient’s cultured leukocytes. CONCLUSION: These results proved the pathogenicity of a novel intronic variant in our patient. We concluded that the minigene assay is a useful, non-invasive method for functional splicing analysis of inherited kidney disease, even if standard transcriptional analysis could not detect abnormal mRNA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12882-017-0774-4) contains supplementary material, which is available to authorized users.